Investigating the impact of mobile SNS addiction on individual's self-rated health. Issue 2 (4th April 2018) - Dong, Yuanyuan; Xue, Yajiong; Luo, Mengyun; Mo, Dandan; Dong, Wei; Zhang, Zhiruo; Liang, Huigang
Abstract : Purpose: The purpose of this paper is to investigate how WeChat addiction influences users' physical, mental, and social health. Design/methodology/approach: A national survey was conducted in China. A total of 1, 058 responses were collected from 31 regions of China. Findings: The regression results show that WeChat addiction is negatively associated with users' physical, mental, and social health. The negative effects are significant even after adjusting for the effects of the Big Five personality traits, years of using WeChat, and demographic variables such as age, gender, education level, and monthly income. Years of using WeChat is not significantly related to users' health. It is also found that the influence of WeChat addiction on health outcomes is sensitive to years of WeChat use. The influence is dormant when users have less than three years of WeChat usage, but starts to exhibit itself after three years. Research limitations/implications: Addictive use of WeChat is associated with declining overall health among Chinese users. Given the cross-sectional nature of this study, definite causal relationship between WeChat addiction and health deterioration cannot be established. Controlled experiments are needed to further examine the causal effects of WeChat addiction. Originality/value: WeChat is the most popular mobile social network service (SNS) in China, but its comprehensive impact on users' health is rarely studied. This paper extends the extant research on SNS addiction by providing a deepened understanding of how mobile SNS addiction affects personal health in the unique context of WeChat, which provides an important contribution to the interdisciplinary research in public health, psychology, and information systems.